Jahresbericht 1976 - Kunstgesellschaft Luzern. - Kunstmuseum Luzern, Luzern (Luzern : Kunstgesellschaft Luzern, 1977)
Kielholz, Heiner ; Adler Petersen, Lene ; Kirkeby, Per ; Stöckli, Paul ; Zorio, Gilberto ; Mol, Pieter ; Henneman, Jeroen ; Bakker, Douwe Jan ; van de Wint, Rudi ; Rous, Martin ; van Koningsbruggen, Rob ; Odermatt, Josef Maria ; Dulk, Markus ; Attersee, Christian Ludwig ; Federle, Helmut ; etc.
Duits
boek